Digital futures for learning speculative methods and pedagogies - Ross, Jen (Routledge, 2023)
"Digital Futures for Learning offers a methodological and pedagogical way forward for researchers and educators who want to work imaginatively with 'what's next' in higher education and informal learning. Today's debates around technological transformations of social, cultural, and educational spaces and practices need to be informed by a more critical understanding of how visions of the future of learning are made and used, and how they come to be seen as desirable, inevitable, or impossible. Integrating innovative methods, key research findings, engaging theories, and creative pedagogies across multiple disciplines, this book argues for and explores speculative approaches to researching and analysing post-compulsory and informal learning futures-where we are, where we might go, and how to get there"--